Ought implies Kant : a reply to the consequentialist critique - Marks, Joel, 1949- (Lexington Books, 2009)
This book offers an unconventional defense of Kantian ethical theory as encompassing moral regard for nonhuman animals and, complementarily, an exhaustive rendition of a relatively neglected refutation of consequentialism as violating an essential meta-ethical condition of theoretical viability.